2017
DOI: 10.7324/rjc.2017.1031861
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis on Nanolubricants Used in Multi Cylinder Petrol Engine With Copper Oxide as Nanoparticle

Abstract: Now a day's, nanoparticles are extensively used to increase the thermal conductivity, heat transfer rate and tribological properties of the engine lubricant by adding nano additives to form nanofluids. Accumulation of nanoparticles in engine lubricant may reduce friction with the improvement of the lubrication characteristics. In order to reduce the friction and wear lubricants are used, but still, the fuel consumed for frictional losses is about ten to twenty percentages of the total fuel supply. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…It was also reported that the engine head bench test was an unfired apparatus so it is difficult to account the effect of nanoparticles in an oxidizing atmosphere commonly present in Internal Combustion Engine. Nallusamy et al [147] in their study reported that the nanoparticles are extensively used to increase the thermal conductivity, heat transfer rate and tribological properties of the engine lubricant by adding nano-additives to form nanofluids. In order to reduce the friction and wear, lubricants are used, but still, the fuel consumed for frictional losses is about ten to twenty percentages of the total fuel supply.…”
Section: Lubricants and Nanoparticles Additives For Automotive Applicationmentioning
confidence: 99%
“…It was also reported that the engine head bench test was an unfired apparatus so it is difficult to account the effect of nanoparticles in an oxidizing atmosphere commonly present in Internal Combustion Engine. Nallusamy et al [147] in their study reported that the nanoparticles are extensively used to increase the thermal conductivity, heat transfer rate and tribological properties of the engine lubricant by adding nano-additives to form nanofluids. In order to reduce the friction and wear, lubricants are used, but still, the fuel consumed for frictional losses is about ten to twenty percentages of the total fuel supply.…”
Section: Lubricants and Nanoparticles Additives For Automotive Applicationmentioning
confidence: 99%
“…The addition of CuO to the sunflower oil increased the coefficient of friction. Hence, it is very clear that the addition of nanoparticles may not always increase the tribological performance of the vegetable oils [26][27][28][29]. The optimum concentration of graphite to be added to the base oil is 0.1% weight.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nanolubricants, a nanofluid class dedicated to lubrication, have shown success in reducing the wear and coefficient of friction in conventional ICE lubricants. [8][9][10][11][12][13] However, their performance has never been discussed and reviewed in terms of EVs' tribological conditions. This study explores the behaviour of various nanolubricants combinations composed of single or several types of nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%